IMPLEMENTASI PEMBELAJARAN BERBASIS PRODUK DALAM RANGKA MENYIAPKAN LULUSAN YANG INOVATIF PADA MAHASISWA PGMI UIN RADEN MAS SAID SURAKARTA - Kustiarini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The use of media in learning has a very important role as a means of non-verbal communication. The importance of using media in the learning process has been stated by many experts. Based on the preliminary studies that had been carried out, it is shown that teachers rarely use and develop learning media. Teachers have lacked sufficient knowledge and skills to develop thematic learning media. It is because of the lack of training in making thematic learning media. Hence, learning activities tend to be monotonous by applying lectures. One of the attempts to produce quality teachers is to equip prospective teacher students with appropriate knowledge and skills based on the era. The PGMI study program teaches students to develop thematic learning media. It was to find out how to implement product-based learning to prepare innovative graduates for the students of PGMI UIN Raden Mas Said Surakarta. The research was descriptive qualitative research. The results of the research were 1) the planning stage, which included the preparation of lesson plans for the PGMI learning system planning and learning materials design, 2) the implementation phase, which included teaching the learning material on thematic learning media and their development, analyzing basic competencies, indicators and thematic learning objectives, designing thematic learning media, and implementing the development of thematic learning media, and 3) evaluation phase that included try-out of thematic learning media use, criticism and suggestions related to the advantages and disadvantages of the thematic learning media products.